The use of wheel torque modulation to mitigate road induced longitudinal vibrations - Bakirci, Ibrahim; Katadzic, Nino (My University, 2014)
Customers often require excellent ride comfort without compromising the handling characteristics. Extensive studies have been performed in the area of vertical motion in order to dissipate the forces from an impact whereas the study on longitudinal motion has not been so comprehensive. The aim of this thesis is to present an analysis of how torque modulation can be used to mitigate the longitudinal vibrations felt by the passengers in the vehicle when it is subjected to impacts through speed lowering obstacles. A study is performed to understand how road disturbances are inducing longitudinal vibrations and forces in the wheel assembly. The typical behaviour of the system is analysed in order to come up with a solution on the problem. The study has mainly been performed in a simulation environment using Simpack as MBS software and the vehicle model has been validated through proving ground tests. In order to enable torque modulation when the vehicle is subjected to an impact, a hypothetical controller is created in Simulink and co-simulated with Simpack. The results show improvement in lowering the high seat rail acceleration peaks of impact harshness although there is room for improvement regarding the controller to make it more stable and robust. A very high torque is requested by the controller however further investigation shows that the torque can be limited to 250 Nm without significantly affecting the improvement of the vibrations caused by the impact. This gives a more realistic torque demand and flexibility in choosing actuators.
Keywords: Transport; Farkostteknik; Transport; Vehicle Engineering